2015
DOI: 10.1155/2015/241793
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pesticidal Activities of 5-(2-Cyclopropylaminopyrimidin-4-yl)-4-(thiophenyl)thiazole Derivatives

Abstract: Pesticidal activities of 4-[5-(2-cyclopropylaminopyrimidin-4-yl)-4-(4-chloro-2-fluoro-phenyl)thiazol-2-yl]-1-methylpiperidine, designated as Comp I, have been determined against a mosquito larva, Culex pipiens pallens, and a phytopathogenic fungus, Phytophthora capsici. Comp I was used as the leading compound in this study. The compounds were synthesized by reacting them with two functional groups, 3-thiophenyl and 2-thiophenyl groups, instead of 4-chloro-2-fluorophenyl group in Comp I. Other functional groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Subsequently, when the terminal group was replaced and the remaining thiazole and piperidine rings in the oxathiapiprolin molecule unchanged (e.g., compounds 6 , 7 , 8 , and 9 ), their fungicidal activities have not been significantly improved, instead of certain insecticidal activities ( Zhu et al, 2016 ; Ding et al, 2019a ; Ding et al, 2019c ; Ding et al, 2020 ). However, Choi et al (2015) reported a novel compound 10 with high fungicidal and insecticidal activities through the modification of the thiazole ring in 2015, with the EC 50 value of 0.98 μM against P. capsici and the LC 50 value of 0.513 μM against Cx. p. pallens .…”
Section: Structural Modification Of Commercial Oxathiapiprolinmentioning
confidence: 99%
“…Subsequently, when the terminal group was replaced and the remaining thiazole and piperidine rings in the oxathiapiprolin molecule unchanged (e.g., compounds 6 , 7 , 8 , and 9 ), their fungicidal activities have not been significantly improved, instead of certain insecticidal activities ( Zhu et al, 2016 ; Ding et al, 2019a ; Ding et al, 2019c ; Ding et al, 2020 ). However, Choi et al (2015) reported a novel compound 10 with high fungicidal and insecticidal activities through the modification of the thiazole ring in 2015, with the EC 50 value of 0.98 μM against P. capsici and the LC 50 value of 0.513 μM against Cx. p. pallens .…”
Section: Structural Modification Of Commercial Oxathiapiprolinmentioning
confidence: 99%